Smart Legal: Proposing Artificial Intelligence Application to Provide Free Legal Aid in Indonesia - Hakim Hary Abdul; Praja Chrisna Bagus Edhita; Setyaningrum Wita; Setiawati Diana (E3S Web of Conferences, 2024)
This study aims to evaluate the efficacy of harnessing Artificial Intelligence (AI) for the provision of free legal aid in Indonesia. The imperative for accessible, dependable, and professional legal aid is recognized as a fundamental right for all individuals, as stipulated by the Indonesian Constitution. Additionally, the state has promulgated legal aid regulations in the form of rules and implementing guidelines, emphasizing the obligation for law enforcers, particularly advocates, to offer free legal assistance to individuals with lower incomes. Employing a literature review methodology, this study draws insights from legal texts, books, journals, and other pertinent sources to analyze the subject comprehensively. The data is qualitatively analyzed and presented descriptively. The findings demonstrate the significant potential of AI to become an integral component in providing sustained and effective free legal aid, particularly in handling large caseloads and enhancing the ability of advocates to uphold public trust. Despite the promising aspects, the study identifies current challenges in the implementation of AI in Indonesia. These challenges include the absence of a legal foundation, a scarcity of human resources, high costs associated with AI deployment, and a general lack of awareness among the public regarding the utilization of AI in the legal profession. Addressing these challenges is crucial to realizing the full potential of AI in advancing the accessibility and quality of free legal aid services in Indonesia.